THE TOPICAL DEFECTS OF THE BRAKING SYSTEM DETECTABLE DURING PERIODIC TECHNICAL INSPECTIONS - MIOTLA, Piotr; Sylwester, GLOD (Trends in education, 2014)
The task of the braking system is creation the braking couples on wheels' axis, which enable in controlled way decrease of the travelling speed or the vehicle immobilization during the stop. One of the fundamental conditions of the road safety is a driver control of the travelling speed all the time. For this reason, the technical condition of the vehicle's braking system allowed the public road traffic cannot arouse reservations. The task of the vehicle inspection station is control among other things all braking system in order to determine its technical condition, wear and tear of some exploitation elements arousing from using the car. The diagnostician informs the driver about the technical condition after fulfillment of the tests. In case of the defectiveness of the braking system elements he orders its immediate change.
Keywords: didactics; technical education; the braking system.